(untitled) (Sambahak: Human Rights Journal, 2025)
Miscarriage of justice is an outcome in a process of justice that is unjust. Justice may be miscarried if there is any serious violation of human rights in any stages of criminal proceedings. Factual innocent and legal innocent people fall into the trap of Miscarriage of justice. The paper aims to explore the situation of miscarriage of justice in pretrial, trial and post-trial stages of criminal proceedings in Nepal. The paper presents the issues related to the miscarriage of justice and sketches how human rights of the parties of the cases are being violated in Nepal. Similarly, this paper has incorporated the existing legal framework to prevent and protect people from miscarriage of justice in Nepal. Ultimately, this paper concludes by stating that the State must enforce the existing legal framework effectively to protect the rights of the people subjected to miscarriage of justice and make other necessary laws for the prevention of miscarriage of justice including effective remedies.